Study cell membrane dynamics using interferometric scattering microscope - Goh, Kheng Ling (Nanyang Technological University, 2024)
This study explored the capabilities of iSCAT microscopy for two applications: monitoring cellular dynamics during fixation and differentiating between cancer cell lines of varying malignancy. For fixation studies, iSCAT successfully tracked changes in membrane dynamics of spiking human embryonic kidney (SHEK) cells exposed to increasing concentrations and durations of formaldehyde. Observed increases in dynamics suggest potential for using iSCAT to investigate fixative effects on cellular processes. In cancer malignancy studies, iSCAT data were collected from various cancer cell lines and analyzed using autocorrelation and histogram techniques. Background calibration was found to be crucial for accurate data interpretation. While initial observations suggested a possible decrease in membrane dynamics with increasing malignancy, these trends lacked statistical significance due to data spread and potential contamination issues. Analysis of PTC and FTC cancer cells revealed significant differences in membrane dynamics, suggesting a potential role for iSCAT in differentiating these cancer subtypes. This distinction was not observed for ATC cells, warranting further investigation. Overall, this study highlights the promise of iSCAT microscopy for studying cellular dynamics. However, further research is needed to optimize iSCAT for cancer malignancy diagnosis. Future studies should address limitations identified here, such as stricter sterility protocols, larger sample sizes, and the inclusion of additional cancer cell lines. Investigating the influence of specific tumor biomarkers on the iSCAT signal could also be valuable for cancer diagnostics.